Dietary sodium intake and all-cause mortality in kidney stone patients: a retrospective cohort study - Shuangning Liu; Yu Dai; Baolei Shi; YanHu Meng; Xiaoke Sun; Yatao Jia (Frontiers in Nutrition)
BackgroundThe long-term effects of dietary sodium intake on patients with kidney stones remain unclear; hence, this study aims to investigate the correlation between dietary sodium intake and all-cause mortality in patients with kidney stones.MethodsThis retrospective cohort study included 2,765 participants from the National Health and Nutrition Examination Survey (NHANES) 2007–2018. The National Death Index (NDI) was utilized to identify all causes of death until December 31, 2018. Hazard ratios (HR) and 95% confidence intervals (CIs) were calculated using multivariate Cox regression models. Subsequently, subgroup analysis, Kaplan–Meier (KM) curves, as well as weighted generalized additive model regression and smooth curve fitting were performed to further evaluate the correlation between dietary sodium intake and all-cause mortality.ResultsOver the 17,901 person-years of observation, a total of 372 deaths were recorded. The baseline characteristics revealed that individuals with elevated dietary sodium intake tended to be younger, Non-Hispanic White people, with a higher educational attainment, stable marital status, higher household income, lower prevalence of coronary heart disease (CHD), and were more inclined to smoking and alcohol consumption compared to participants with lower sodium intake (<2.2 g/d) (p < 0.01). In the fully adjusted Model 4, a significant inverse relationship between dietary sodium intake (DSI) and all-cause mortality risk was observed when DSI was analyzed as a continuous variable (HR = 0.89, 95% CI = 0.80–0.99, p = 0.034). When DSI was treated as a categorical variable, individuals with a DSI ≥ 2.2 g/day exhibited a reduced risk of all-cause mortality compared to the lowest sodium intake group (DSI < 2.2 g/d). The relationship between dietary sodium intake and all-cause mortality in kidney stone patients demonstrated a linear association, with an 11% decrease in the risk of all-cause mortality observed for each additional unit-g/d increase in dietary sodium intake.ConclusionHigher dietary sodium intake levels were associated with lower all-cause mortality in kidney stone patients within the United States population. Notably, our results contradict the currently widely advocated recommendation to reduce sodium intake. Nonetheless, this observational study alone is insufficient to support any specific dietary recommendations.